Konsep Riba Dalam Perekonomian Islam - Komala Dewi (Journal of Islamic Economics and Finance, 2024)
: This article describes the problem of usury from a legal perspective and its interpretation as well as bank interest from a review of Islamic law and analyzes its impact on the economy, both those raised by Islamic law experts, mufassirin and Muslim economists. The prohibition of usury in Islam is expressly stated in both the Qur'an and the Hadith which were revealed gradually. The prohibition of riba (usurios) in Islam is based on moral and humanitarian considerations because the essence of the prohibition of usury is the elimination of all forms of economic practices that give rise to tyranny and injustice. And the impact of interest on the economy will hamper economic growth. The method of writing this article is based on literature review by conducting an in-depth review of books, commentaries and writings on bank interest, usury and related matters. The purpose of this paper is to find out the interpretation of usury and the opinions of scholars regarding bank interest law and to analyze the negative impact that the interest system has on the economy.